Q&A with Michelle Giuda, U.S. Asst. Sec of State, Bureau of Public Affairs - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
President Trump “has right to call out unfair and inaccurate news”. It is up to Americans to decide and have “a healthy debate”.